Electrolyte for lithium secondary battery and lithium secondary battery comprising same

By using an electrolyte containing non-aqueous solvents, lithium salts, nitrates/esters and aryl derivatives in lithium-sulfur batteries, the reduction reaction pathway of lithium sulfide is changed, thereby solving the capacity fading of lithium-sulfur batteries during repeated charge and discharge cycles. problem, achieving high energy density and good capacity retention performance.

CN119343802APending Publication Date: 2025-01-21LG ENERGY SOLUTION LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380044885.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-12-23
Filing Date
2023-12-13
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

Lithium-sulfur batteries have capacity decay problems during repeated charge and discharge cycles, resulting in a rapid reduction in battery energy density.

Method used

An electrolyte containing non-aqueous solvents, lithium salts, nitrates/esters and aryl derivatives is used to inhibit the dissolution of lithium polysulfide by changing the reduction reaction pathway of lithium sulfide, thereby improving the capacity retention rate and performance of the battery. Coulombic efficiency.

Benefits of technology

It effectively inhibits the dissolution of lithium polysulfide, slows down the degradation rate of the battery during repeated charge and discharge cycles, improves the Coulombic efficiency and capacity retention performance of the battery, and achieves high energy density.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119343802A_ABST
    Figure CN119343802A_ABST
Patent Text Reader

Abstract

The present disclosure relates to an electrolyte for a lithium-sulfur battery, the electrolyte comprising a non-aqueous solvent, a lithium salt, a nitrate / ester and an aryl derivative, the non-aqueous solvent comprising a linear ether compound and a conjugated heterocyclic compound, and the aryl derivative includes a compound represented by Chemical Formula 1, a compound represented by Chemical Formula 2, a compound represented by Chemical Formula 3, or a mixture of two or more thereof, whereby the electrolyte solution can exhibit an effect of effectively improving a capacity fade problem in repeated charge-discharge cycles of a battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to an electrolyte for a lithium secondary battery and a lithium secondary battery including the electrolyte.

[0002] More particularly, the present disclosure relates to an electrolyte suitable for a lithium-sulfur battery and a lithium-sulfur battery including the electrolyte.

[0003] This application claims priority to Korean Patent Application No. 10-2022-0183773 filed in Korea on December 23, 2022, the disclosure of which is incorporated herein by reference. Background Art

[0004] Lithium-sulfur batteries are battery systems that use a sulfur-sulfur (SS) bonded sulfur-based material as a positive electrode active material and lithium metal as a negative electrode active material. Sulfur, the main component of the positive electrode active material, exists in large quantities in nature and can be found all over the world. It is non-toxic and has a low atomic weight.

[0005] As secondary batteries are used in a wide range of applications including electric vehicles (EVs) and energy storage systems (ESSs), lithium-sulfur battery technology, which achieves higher energy storage density by weight (~2600 Wh / kg) than lithium-ion secondary batteries having a lower energy storage density by weight (~250 Wh / kg), has attracted attention.

[0006] During discharge, the lithium-sulfur battery is oxidized by releasing electrons to become lithium cations at the negative electrode active material (lithium), and reduced by accepting electrons at the positive electrode active material (sulfur-based material). Through the reduction reaction, the sulfur-based material accepts two electrons through the SS bond and is converted into sulfur anions. The lithium cations generated by the oxidation reaction of lithium migrate to the positive electrode via the electrolyte and combine with the sulfur anions generated by the reduction reaction of the sulfur-based compound to form a salt. Specifically, the sulfur before discharge has a cyclic S8 structure, which is converted into lithium polysulfide (LiS) through the reduction reaction. x ) and is completely reduced to lithium sulfide (Li2S).

[0007] In this case, since the conductivity of sulfur in the sulfur-based compound as a positive electrode active material is low, it is difficult to ensure reactivity with electrons and lithium ions in the solid state. Therefore, in order to improve the reactivity of sulfur in lithium-sulfur batteries, a method for generating an intermediate polysulfide Li2S has been developed. x A technique for inducing liquid phase reaction and improving reactivity. The technique uses an ether solvent such as dioxolane, dimethoxyethane (DME), etc., in which lithium polysulfide is highly soluble, as a solvent for the electrolyte. Therefore, the amount of the electrolyte affects the reactivity of sulfur and the battery life.

[0008] In addition, during the discharge of lithium-sulfur batteries, polysulfide (PS) generated from the positive electrode dissolves into the electrolyte, causing a reaction, and polysulfide causes side reactions in the battery, leading to battery degradation. Although the theoretical density is high, the energy density decreases rapidly during repeated charge and discharge cycles.

[0009] Therefore, there is a need for a technology that suppresses capacity decay during repeated charge and discharge cycles and improves capacity retention. Summary of the invention

[0010] Technical issues

[0011] An object of the present inventors is to provide a lithium-sulfur battery which suppresses capacity fading and improves capacity retention in repeated charge and discharge cycles.

[0012] To this end, the present disclosure aims to provide an electrolyte for a lithium-sulfur battery, which is used to change the reaction pathway of sulfur (S) to control the dissolution of polysulfide (PS), thereby solving the problems caused by the dissolution of polysulfide, such as battery capacity decay.

[0013] Therefore, the present disclosure aims to provide a lithium-sulfur battery with improved capacity retention and high energy efficiency.

[0014] Technical Solution

[0015] In order to achieve the above-mentioned object, according to one aspect of the present disclosure, an electrolyte for a lithium secondary battery according to the following embodiments is provided.

[0016] The electrolyte for a lithium secondary battery according to the first embodiment includes a non-aqueous solvent, a lithium salt, a nitrate, and an aryl derivative, wherein the non-aqueous solvent includes a linear ether compound and a conjugated heterocyclic compound, and wherein the aryl derivative includes a compound represented by the following Chemical Formula 1, a compound represented by the following Chemical Formula 2, a compound represented by the following Chemical Formula 3, or a mixture thereof:

[0017] [Chemical formula 1]

[0018] R1-S-

[0019] [Chemical formula 2]

[0020] R2-SH

[0021] [Chemical formula 3]

[0022] R3-SS-R4

[0023] In the chemical formulae 1 to 3, R1 to R4 are each independently a 5- or 6-membered heteroaryl group containing at least one N or S atom as a ring atom.

[0024] According to the second embodiment, in the first embodiment, R1 to R4 may each independently be an orthopyridyl group.

[0025] According to a third embodiment, in the first or second embodiment, the aryl derivative may include 2,2 -Bispyridyl disulfide.

[0026] According to a fourth embodiment, in any one of the first to third embodiments, the aryl derivative may be included in an amount of 0.1 wt % to 5 wt % based on the total weight of the electrolyte for a lithium-sulfur battery.

[0027] According to a fifth embodiment, in any one of the first to fourth embodiments, the aryl derivative may be included in an amount of 1 wt % to 3 wt % based on the total weight of the electrolyte for a lithium-sulfur battery.

[0028] According to a sixth embodiment, in any one of the first to fifth embodiments, a weight ratio of the aryl derivative to the nitrate (the aryl derivative / the nitrate) may be 0.2 to 1.5.

[0029] According to a seventh embodiment, in any one of the first to sixth embodiments, the linear ether compound and the conjugated heterocyclic compound may be contained in an amount of 80% by volume or more based on the total weight of the nonaqueous solvent.

[0030] According to an eighth embodiment, in any one of the first to seventh embodiments, the conjugated heterocyclic compound may be a conjugated cyclic ether compound.

[0031] According to a ninth embodiment, in any one of the first to eighth embodiments, the nonaqueous solvent may not include a carbonate-based solvent.

[0032] According to a tenth embodiment, in any one of the first to ninth embodiments, the cation of the nitrate may be an alkali metal.

[0033] According to another aspect of the present disclosure, a lithium secondary battery of the following embodiment is provided.

[0034] According to an eleventh embodiment, the lithium secondary battery includes a positive electrode; a negative electrode; a separator located between the positive electrode and the negative electrode; and an electrolyte, wherein the electrolyte is defined in any one of the first to tenth embodiments.

[0035] According to a twelfth embodiment, in the eleventh embodiment, the positive electrode may include a sulfur-containing compound as a positive electrode active material.

[0036] According to the thirteenth embodiment, in the eleventh or twelfth embodiment, the sulfur-containing compound may include inorganic sulfur (S8), lithium (poly) sulfide (Li2S n , 1≤n≤8), carbon-sulfur polymer ((C2S x ) m , 2.5≤x≤50, 2≤m) or a mixture thereof.

[0037] According to a fourteenth embodiment, in any one of the eleventh to thirteenth embodiments, the negative electrode includes lithium metal, lithium alloy, or a mixture thereof as a negative electrode active material.

[0038] According to a fifteenth embodiment, in any one of the eleventh to fourteenth embodiments, the lithium secondary battery may be a coin-type battery, a pouch-type battery, or a cylindrical battery.

[0039] Beneficial Effects

[0040] The electrolyte for a lithium-sulfur battery according to an embodiment of the present disclosure may change the reduction reaction pathway of lithium sulfide, thereby changing the discharge mechanism of the lithium-sulfur battery.

[0041] In particular, the capacity decay of the battery caused by the dissolution of lithium polysulfide into the electrolyte can be suppressed, thereby slowing down the degradation rate of the battery in repeated charge and discharge cycles and correspondingly improving the coulombic efficiency of the battery and the capacity retention performance of the battery.

[0042] Therefore, according to one embodiment of the present disclosure, a lithium-sulfur battery having a high energy density, for example, an energy density of 300 Wh / kg or more, further an energy density of 400 Wh / kg or more can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 The measurement results of the cycle number at which a capacity retention rate of 90% is achieved in repeated charge and discharge cycles in Example 1, Example 2, and Comparative Example 1 are shown.

[0044] Figure 2 The change in coulombic efficiency per unit weight as a function of charge and discharge cycles in Example 1, Example 2, and Comparative Example 1 is shown.

[0045] Figure 3 The measurement results of the cycle number at which a capacity retention rate of 90% is achieved in repeated charge and discharge cycles in Example 1, Comparative Example 3, and Comparative Example 4 are shown. DETAILED DESCRIPTION

[0046] Hereinafter, the present disclosure will be described in more detail.

[0047] It should be understood that the terms or words used in the specification and the appended claims should not be construed as limited to the general and dictionary meanings, but should be interpreted based on the principle that allows the inventor to appropriately define the terms for the best interpretation, and based on the meanings and concepts corresponding to the technical aspects of the present disclosure.

[0048] The terms used herein are for the purpose of describing particular embodiments only and are not intended to limit the present disclosure. As used herein, the singular forms also include the plural forms unless the context clearly indicates otherwise. It should be understood that when the term "comprising" or "including" is used in this specification, the presence of the specified features, numbers, steps, operations, elements, components, or combinations thereof is designated, but the presence or addition of one or more other features, numbers, steps, operations, elements, components, or combinations thereof is not excluded.

[0049] As used herein, the term "composite" refers to a material formed by combining two or more materials and having physically and chemically distinct phases and more effective functions.

[0050] As used herein, the term "(poly)sulfide" encompasses the concepts of "(poly)sulfide ions (S x 2- , 1≤x≤8)" and "lithium (poly)sulfide (Li2S x or Li2S x - 1≤x≤8)".

[0051] As used herein, the term "polysulfide" encompasses the concepts of "polysulfide ions (S x 2- , 1<x≤8)" and "lithium polysulfide (Li2S x or Li2S x - 1<x≤8)".

[0052] Lithium secondary batteries, particularly lithium-sulfur batteries, suffer from rapid capacity fade during repeated charge-discharge cycles due to the shuttle effect of lithium polysulfide dissolved from the positive electrode into the electrolyte during charge and discharge.

[0053] One aspect of the present disclosure aims to solve the above problems.

[0054] Electrolyte for lithium secondary batteries

[0055] Therefore, the present disclosure relates to an electrolyte for lithium secondary batteries for solving the above problems.

[0056] The electrolyte for lithium secondary batteries of the present disclosure includes a non-aqueous solvent, a lithium salt, a nitrate / ester, and an aryl derivative.

[0057] The nonaqueous solvent includes a linear ether compound and a conjugated heterocyclic compound.

[0058] The aryl derivative includes a compound represented by the following Chemical Formula 1, a compound represented by the following Chemical Formula 2, a compound represented by the following Chemical Formula 3, or a mixture thereof.

[0059] [Chemical formula 1]

[0060] R1-S -

[0061] [Chemical formula 2]

[0062] R2-SH

[0063] [Chemical formula 3]

[0064] R3-SS-R4

[0065] In the above Chemical Formulae 1 to 3, R1 to R4 are each independently a 5- or 6-membered heteroaryl group containing at least one N or S atom as a ring atom.

[0066] In the present disclosure, the compound represented by the above Chemical Formula 1 may generally include a thiolate compound.

[0067] In the present disclosure, the compound represented by the above Chemical Formula 2 may generally include a thiol compound.

[0068] In the present disclosure, the compound represented by the above Chemical Formula 3 may generally include a disulfide compound.

[0069] According to one aspect of the present disclosure, the aryl derivative can inhibit the irreversible reaction of lithium polysulfide dissolved from the cathode of the lithium-sulfur battery into the electrolyte, thereby effectively inhibiting the capacity decay of the battery caused by the shuttle effect of lithium polysulfide.

[0070] In the present disclosure, the heteroaryl group is an aromatic cyclic compound, and is a general term for organic compounds containing atoms of other elements other than carbon as ring atoms. In particular, in the present disclosure, R1 to R4 are each independently a 5- or 6-membered heteroaryl group containing at least one N or S atom as a ring atom.

[0071] In one embodiment of the present disclosure, the heteroaryl groups R1 to R4 may each be bonded to -S - , -SH or -SS- functional groups, and in this case, the functional groups can each independently be substituted in the heteroaryl group at the ortho-, meta- or para-position to the heteroatom.

[0072] In another embodiment of the present disclosure, the heteroaryl groups R1 to R4 may each be bonded to -S- , -SH or -SS- functional groups, and in this case, the functional groups may each independently be substituted in the heteroaryl group at the ortho position of the heteroatom.

[0073] According to one embodiment of the present disclosure, R1 to R4 may each independently be an ortho-pyridyl group.

[0074] In one embodiment of the present disclosure, the aryl derivative may include 2,2 -Bispyridyl disulfide.

[0075] In one embodiment of the present disclosure, the electrolyte for a lithium-sulfur battery may include the aryl derivative in an amount of 0.1 wt % to 5 wt % based on the total weight of the electrolyte for a lithium-sulfur battery. For example, the content of the aryl derivative may be 0.1 wt % to 3 wt %, or 0.5 wt % to 3 wt %, 0.5 wt % to 2 wt %, 0.5 wt % to 1.5 wt %, or 1.0 wt % to 1.5 wt %, based on the total weight of the electrolyte for a lithium-sulfur battery. When the amount of the aryl derivative is within the above range, the aryl derivative may be advantageous in terms of the efficiency of improving the capacity retention rate of the lithium-sulfur battery, but the present disclosure is not limited thereto.

[0076] In one embodiment of the present disclosure, the weight ratio of the aryl derivative to the nitrate (aryl derivative / nitrate) may be 0.2 to 1.5. Specifically, the weight ratio of the aryl derivative to the nitrate (aryl derivative / nitrate) may be 0.2 to 1.0, 0.2 to 0.5, 0.2 to 0.3, 0.25 to 0.5, or 0.25 to 0.3. When the weight ratio of the aryl derivative to the nitrate is within the above range, the aryl derivative may be advantageous in terms of the efficiency of improving the capacity retention rate of the lithium-sulfur battery, but the present disclosure is not limited thereto.

[0077] In addition to the lithium salt, when the nitrate / ester is dissolved in the electrolyte for the lithium secondary battery, the nitrate / ester can provide ions, thereby improving the conductivity of the lithium secondary battery, and when the electrolyte for the lithium secondary battery is used in the lithium sulfur battery, the life characteristics of the battery are improved. Specifically, the effect of the nitrate / ester is not limited thereto, but for example, the nitrate / ester can inhibit the reduction reaction of lithium polysulfide during the charge and discharge of the lithium sulfur battery, thereby preventing the irreversible consumption of lithium polysulfide, thereby leading to the improvement of the performance of the lithium sulfur battery.

[0078] In one embodiment of the present disclosure, the nitrate / ester may include, but is not limited to, any type of nitrate / ester that forms a stable coating on the negative electrode of a lithium secondary battery, specifically the lithium sulfur battery, i.e., the lithium metal electrode, and improves the charge and discharge efficiency, and may include, for example, nitric acid compounds, nitrite compounds, or mixtures thereof.

[0079] In one embodiment of the present disclosure, the nitrate / ester can be, for example, selected from the group consisting of: inorganic nitric acid or nitrous acid compounds, such as lithium nitrate (LiNO3), potassium nitrate (KNO3), cesium nitrate (CsNO3), barium nitrate (Ba(NO3)2), ammonium nitrate (NH4NO3), lithium nitrite (LiNO2), potassium nitrite (KNO2), cesium nitrite (CsNO2), ammonium nitrite (NH4NO2); organic nitric acid or nitrous acid compounds, such as methyl nitrate, dialkylimidazolium nitrate, guanidine nitrate, imidazolium nitrate, pyridinium nitrate, ethyl nitrite, propyl nitrite, butyl nitrite, amyl nitrite, octyl nitrite; organic nitro compounds, such as nitromethane, nitropropane, nitrobutane, nitrobenzene, dinitrobenzene, nitropyridine, dinitropyridine, nitrotoluene, dinitrotoluene and combinations thereof, but are not limited thereto.

[0080] In one embodiment of the present disclosure, the cation of the nitrate may be selected from alkali metals such as lithium, sodium, potassium, rubidium, and cesium, but is not limited thereto.

[0081] In another embodiment of the present disclosure, the nitrate may comprise lithium nitrate (LiNO 3 ).

[0082] In one embodiment of the present disclosure, based on the total weight of the lithium secondary battery electrolyte, the content of the nitrate / ester may be, for example, 1 wt % to 10 wt %, 2 wt % to 10 wt %, or 3 wt % to 10 wt %, specifically 3 wt % to 8 wt %, 3 wt % to 6 wt %, or 3 wt % to 5 wt %, but is not limited thereto. When the nitrate / ester is included in the above amount, when used in the lithium sulfur battery, the nitrate / ester may have a favorable effect on the conductivity of the electrolyte and the reduction inhibition of polysulfides, but the present disclosure is not limited thereto.

[0083] According to one aspect of the present disclosure, the nonaqueous solvent is a medium for movement of ions participating in an electrochemical reaction of the lithium secondary battery, and is used to dissolve the lithium salt, the nitrate, and / or the aryl derivative.

[0084] In order to achieve the above effects, according to the present disclosure, the nonaqueous solvent includes a linear ether compound and a conjugated heterocyclic compound.

[0085] In one embodiment of the present disclosure, the non-aqueous solvent may contain 80% by volume or more, such as 85% to 100% by volume, 90% to 100% by volume, 95% to 100% by volume, 98% to 100% by volume, 90% to 98% by volume, or 90% to 95% by volume of the linear ether compound and the conjugated heterocyclic compound, based on the total volume of the non-aqueous solvent. When the amount of these two types of compounds is within the above range based on the total volume of the non-aqueous solvent, the solubility of the lithium salt, the nitrate / ester and the aryl derivative may be favorably affected, but the present disclosure is not limited thereto.

[0086] In one embodiment of the present disclosure, the non-aqueous solvent may further include cyclic ethers in addition to the linear ethers.

[0087] In one embodiment of the present disclosure, the linear ether may include, for example, at least one selected from the group consisting of dimethyl ether, diethyl ether, dipropyl ether, dibutyl ether, diisobutyl ether, ethyl methyl ether, ethyl propyl ether, ethyl tert-butyl ether, dimethoxymethane, trimethoxymethane, dimethoxyethane, diethoxyethane, dimethoxypropane, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, ethylene glycol divinyl ether, diethylene glycol divinyl ether, triethylene glycol divinyl ether, dipropylene glycol dimethyl ether, butylene glycol ether, diethylene glycol ethyl methyl ether, diethylene glycol isopropyl methyl ether, diethylene glycol butyl methyl ether, diethylene glycol tert-butyl ethyl ether and ethylene glycol ethyl methyl ether. Preferably, the linear ether may include at least one selected from the group consisting of dimethyl ether, dimethoxyethane, diethoxyethane, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether and tetraethylene glycol dimethyl ether, more preferably, dimethoxyethane.

[0088] In one embodiment of the present disclosure, the conjugated heterocyclic compound is a general term for compounds having the following structure: wherein the p orbitals of three or more adjacent atoms of the compound and other p orbitals of adjacent atoms connected by σ bonds can overlap, and atoms other than carbon are included in the structure as ring atoms.

[0089] In one embodiment of the present disclosure, due to the inclusion of the conjugated heterocyclic compound as the non-aqueous solvent, in the initial discharge stage of the battery, the heterocyclic compound forms a polymer passivation layer (solid electrolyte interface (SEI) layer) on the surface of the lithium-based metal (negative electrode) through a ring-opening reaction, thereby inhibiting the growth of lithium dendrites. In addition, it can reduce the electrolyte decomposition on the surface of the lithium-based metal and the side reactions caused by it, thereby extending the life of the lithium-sulfur battery. In addition, since the lone pair of electrons of the heteroatom (usually the sulfur atom) is delocalized through the conjugated structure, it is difficult to dissolve the salt, thereby reducing the amount of polysulfide dissolved into the electrolyte.

[0090] In one embodiment of the present disclosure, the conjugated heterocyclic compound may be a 4-15-membered, preferably 4-7-membered, more preferably 5-6-membered heterocyclic compound. In addition, the conjugated heterocyclic compound may be at least one substituted or unsubstituted heterocyclic compound selected from the group consisting of: an alkyl group having 1 to 4 carbon atoms, a cycloalkyl group having 3 to 8 carbon atoms, an aryl group having 6 to 10 carbon atoms, a halogen, a nitro group (-NO2), an amine group (-NH2) or a sulfonyl group (-SO2). In addition, the conjugated heterocyclic compound may be a polycyclic compound of the heterocyclic compound and at least one of a cycloalkyl group having 3 to 8 carbon atoms or an aryl group having 6 to 10 carbon atoms.

[0091] When the conjugated heterocyclic compound is substituted with an alkyl group having 1 to 4 carbon atoms, the free radical is stabilized, thereby suppressing the side reaction derived from the decomposition of the electrolyte. In addition, when the conjugated heterocyclic compound is substituted with a halogen group or a nitro group, a functional protective layer can be preferably formed on the surface of the lithium-based metal, and in this case, the functional protective layer can be stable as a protective layer in a compressed form, and the lithium-based metal can be uniformly deposited, and the side reaction between the polysulfide and the lithium-based metal can be suppressed.

[0092] In one embodiment of the present disclosure, the conjugated heterocyclic compound may include at least one of a conjugated cyclic ether compound or a thiophene-based compound.

[0093] In one embodiment of the present disclosure, the conjugated cyclic ether compound may include, for example, a furan-based compound and a pyran-based compound, more specifically, furan, 2-methylfuran, 3-methylfuran, 2-ethylfuran, 2-propylfuran, 2-butylfuran, 2,3-dimethylfuran, 2,4-dimethylfuran, 2,5-dimethylfuran, pyran, 2-methylpyran, 3-methylpyran, 4-methylpyran, benzofuran, 2-(2-nitrovinyl)furan, or a mixture thereof, but is not limited thereto.

[0094] In one embodiment of the present disclosure, the thiophene-based compound may include, for example, thiophene, 2-methylthiophene, 2-ethylthiophene, 2-propylthiophene, 2-butylthiophene, 2,3-dimethylthiophene, 2,4-dimethylthiophene and 2,5-dimethylthiophene or a mixture thereof, but is not limited thereto.

[0095] In one embodiment of the present disclosure, in addition to the linear ether and the conjugated heterocyclic compound, the nonaqueous solvent may further include a non-conjugated cyclic ether. The non-conjugated cyclic ether may include, for example, at least one selected from the group consisting of 1,3-dioxolane, 4,5-dimethyl-dioxolane, 4,5-diethyl-dioxolane, 4-methyl-1,3-dioxolane, 4-ethyl-1,3-dioxolane, tetrahydrofuran, 2-methyltetrahydrofuran, 2,5-dimethyltetrahydrofuran, 2,5-dimethoxytetrahydrofuran, 2-ethoxytetrahydrofuran, 2-methyl-1,3-dioxolane, 2-vinyl-1,3-dioxolane, 2,2-dimethyl-1,3-dioxolane, 2-methoxy-1,3-dioxolane, 2-ethyl-2-methyl-1,3-dioxolane, tetrahydropyran, 1,4-dioxane, 1,2-dimethoxybenzene, 1,3-dimethoxybenzene, 1,4-dimethoxybenzene and dimethyl isosorbide. Preferably, the non-conjugated cyclic ether may include at least one selected from the group consisting of 1,3-dioxolane, tetrahydrofuran, 2-methyltetrahydrofuran, and 2,5-dimethyltetrahydrofuran, but is not limited thereto.

[0096] In one embodiment of the present disclosure, the non-aqueous solvent may include 1,2-dimethoxyethane and 2-methylfuran.

[0097] In addition, the non-aqueous solvent may contain the linear ether and the conjugated heterocyclic compound in a volume ratio of 95:5 to 5:95, preferably 95:5 to 50:50, most preferably 90:10 to 70:30 or 80:20. The volume ratio is the ratio of "volume % of the linear ether" to "volume % of the conjugated heterocyclic compound" in the non-aqueous solvent.

[0098] In one embodiment of the present disclosure, on the basis of containing the linear ether, the conjugated heterocyclic compound and the non-conjugated cyclic ether compound, the non-aqueous solvent may also contain any organic solvent that dissolves the lithium salt, the nitrate / ester and the aryl derivative, for example, any organic solvent used in the electrolyte of a lithium secondary battery, such as esters, amides, linear carbonates and cyclic carbonates. In one embodiment of the present disclosure, on the basis of containing the ether-based solvent, the non-aqueous solvent may also contain any non-aqueous solvent used in the electrolyte of a lithium secondary battery. However, preferably, in terms of the solubility of the lithium salt, the nitrate / ester and the aryl derivative, the electrolyte for the lithium secondary battery may not contain a carbonate-based solvent as the non-aqueous solvent.

[0099] In one embodiment of the present disclosure, the ester may include, for example, any one selected from the group consisting of methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, γ-valerolactone, γ-caprolactone, σ-valerolactone and ε-caprolactone, or a mixture thereof, but is not limited thereto.

[0100] In one embodiment of the present disclosure, the linear carbonate may generally include, for example, any one selected from the group consisting of dimethyl carbonate, diethyl carbonate, dipropyl carbonate, ethyl methyl carbonate, methyl propyl carbonate and ethyl propyl carbonate, or a mixture thereof, but is not limited thereto.

[0101] In one embodiment of the present disclosure, the cyclic carbonate comprises any one or a mixture thereof selected from the group consisting of ethylene carbonate, propylene carbonate, 1,2-butylene carbonate, 2,3-butylene carbonate, 1,2-pentylene carbonate, 2,3-pentylene carbonate, vinylene carbonate, vinyl ethylene carbonate and its halide. In addition, the halide may include, for example, fluoroethylene carbonate, but is not limited thereto.

[0102] In another embodiment of the present disclosure, the nonaqueous solvent may not include a carbonate-based solvent because the carbonate-based solvent does not dissolve the nitrate and / or the aryl derivative or has low solubility.

[0103] In one embodiment of the present disclosure, the non-aqueous solvent may contain the carbonate-based solvent in such a small amount that the carbonate-based solvent does not affect the solubility of the nitrate / ester and / or the aryl derivative. For example, when the non-aqueous solvent contains the carbonate-based solvent, the amount of the carbonate-based solvent may be less than 3 wt %, less than 2 wt %, less than 1 wt %, 0.5 wt % or 0 wt % (i.e., zero) based on the total weight of the lithium secondary battery electrolyte.

[0104] In one aspect of the present disclosure, the lithium salt may include any lithium salt commonly used in the electrolyte of a lithium-sulfur battery without limitation. The lithium salt may include, for example, LiCl, LiBr, LiI, LiClO4, LiBF4, LiB 10 Cl 10 , LiPF6, LiCF3SO3, LiCF3CO2, LiC4BO8, LiAsF6, LiSbF6, LiAlCl4, CH3SO3Li, CF3SO3Li, (CF3SO2)2NLi, (C2F5SO2)2NLi, (SO2F)2NLi, (CF3SO2)3CLi, lithium chloroborate, lithium lower aliphatic carboxylate, lithium tetraphenylborate, lithium imide or mixtures thereof, but not limited thereto.

[0105] In one embodiment of the present disclosure, the lithium salt may not include lithium nitrate. As an example of the above nitrate / ester, lithium nitrate may be included.

[0106] In one embodiment of the present disclosure, the lithium salt may include lithium bis(fluorosulfonyl)imide (LiFSI).

[0107] In one embodiment of the present disclosure, the concentration of the lithium salt may be appropriately determined in consideration of ion conductivity and solubility, and may be, for example, 0.1 to 4.0 M, 0.25 to 3.0 M, 0.5 to 2.0 M, 0.5 to 1.0 M, or 0.5 to 0.75 M. When the concentration of the lithium salt is within the above range, it may have a favorable effect on the ion conductivity and viscosity of the electrolyte, but is not limited thereto.

[0108] In another embodiment of the present disclosure, on the basis of the above composition, the electrolyte for lithium-sulfur battery may further include additives to improve charge and discharge characteristics and flame retardancy. The present disclosure is not limited to a specific type of additive, but the additive may include, for example, pyridine, triethyl phosphite, triethanolamine, ethylenediamine, n-glyme, hexamethylphosphoric triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidinones, ammonium salts, pyrrole, 2-methoxyethanol, aluminum chloride, fluoroethylene carbonate (FEC), propylene sultone (PRS) and vinylene carbonate (VC).

[0109] The electrolyte for a lithium-sulfur battery according to one aspect of the present disclosure may be prepared by a method commonly used in the art, and the present disclosure is not limited to a specific method.

[0110] Lithium-sulfur battery

[0111] A lithium-sulfur battery according to another aspect of the present disclosure comprises the above-mentioned lithium-sulfur battery electrolyte, a positive electrode comprising a positive electrode active material, and a negative electrode comprising a negative electrode active material. Specifically, the positive electrode active material comprises elemental sulfur, a sulfur compound, or a mixture thereof.

[0112] positive electrode

[0113] The positive electrode may include a positive electrode current collector and a positive electrode active material layer on one or both surfaces of the positive electrode current collector.

[0114] The positive electrode current collector is not limited to a specific type, and may include any positive electrode current collector that supports the positive electrode active material and has high conductivity without causing any chemical changes in the battery. For example, the positive electrode current collector may include copper, stainless steel, aluminum, nickel, titanium, palladium, sintered carbon, copper or stainless steel whose surface is treated with carbon, nickel or silver, aluminum-cadmium alloy, etc.

[0115] The positive electrode current collector may have fine concavoconvexities on the surface to increase the bonding strength with the positive electrode active material, and may have various forms, for example, a film, a sheet, a foil, a mesh, a net, a porous body, a foam, a non-woven fabric, and the like.

[0116] The positive electrode active material layer includes the positive electrode active material, and may further include a conductive material, a binder, and an additive.

[0117] The positive electrode active material may include a sulfur-carbon composite, which includes a porous carbon material and sulfur in at least a portion of the interior of the porous carbon material and the outer surface of the porous carbon material. Since the sulfur contained in the positive electrode active material itself does not have conductivity, sulfur is used in combination with a conductive material such as a carbon material. Therefore, the sulfur is contained in the form of a sulfur-carbon composite.

[0118] In one embodiment of the present disclosure, the positive electrode active material may include elemental sulfur, a sulfur compound or a mixture thereof. Specifically, the positive electrode active material may include inorganic sulfur (S8), lithium (poly) sulfide (Li2S n , 1≤n≤8), disulfide compounds, organic sulfur compounds, carbon-sulfur polymers ((C2S x ) n , x=2.5 to 50, 2≤n) or a mixture thereof. Preferably, the sulfur may be inorganic sulfur.

[0119] The sulfur-carbon composite includes the porous carbon material to provide a framework for uniformly and stably fixing sulfur and to compensate for low electrical conductivity of the sulfur, thereby enhancing an electrochemical reaction.

[0120] The porous carbon material can generally be prepared by carbonizing various carbon precursors. The porous carbon material contains irregular pores. The average diameter of the pores can be in the range of 1 to 200 nm, and the porosity can be in the range of 10 to 90 volume % of the total volume of the porous carbon material. When the average diameter of the pores is less than the above range, the pore size is only at the molecular level, making it impossible to load sulfur. On the contrary, when the average diameter of the pores exceeds the above range, it is not suitable for electrode manufacturing processes due to the low mechanical strength of the porous carbon material.

[0121] In one embodiment of the present disclosure, the "average diameter of the pores" can be measured by known methods for measuring the pore diameter of porous materials, and the measuring method is not particularly limited. For example, the pore size can be measured by electron scanning microscopy (SEM), field emission electron microscopy or laser diffraction. Measurement using laser diffraction can be performed, for example, using a commercially available laser diffraction particle size analyzer (e.g., Microtrac MT 3000).

[0122] In one embodiment of the present disclosure, "porosity" refers to the ratio of the volume occupied by the pores to the total volume of the structure, in %, and can be used interchangeably with the terms porosity, void ratio, etc. In the present disclosure, the method for measuring the porosity is not particularly limited. According to one embodiment of the present disclosure, the porosity can be measured by the BET method using nitrogen, mercury (Hg) porosimetry, or ASTM D2873.

[0123] The porous carbon material may be in the shape of a sphere, a rod, a needle, a plate, a tube or a block, and is not limited to a specific shape, and may be any shape commonly used in lithium-sulfur batteries.

[0124] The porous carbon material may include any porous carbon material commonly used in the art having a porous structure and a large specific surface area. For example, the porous carbon material may include at least one selected from the group consisting of: graphite; graphene; carbon black, such as Denka black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, etc.; carbon nanotubes (CNTs), such as single-walled carbon nanotubes (SWCNTs), multi-walled carbon nanotubes (MWCNTs), etc.; carbon fibers, such as graphite nanofibers (GNFs), carbon nanofibers (CNFs), activated carbon fibers (ACFs), etc.; graphites, such as natural graphite, artificial graphite, expandable graphite, etc.; and activated carbon, but not limited thereto. Preferably, the porous carbon material may be a carbon nanotube.

[0125] In the sulfur-carbon composite according to the present disclosure, the sulfur may be arranged in at least one of the interior of the porous carbon material or the outer surface of the porous carbon material, for example, it may be present in an area of ​​less than 100%, preferably 1% to 95%, and more preferably 40% to 96% of the interior of the porous carbon material and the outer surface of the porous carbon material. When the sulfur is present in the interior of the porous carbon material and the outer surface of the porous carbon material within the above range, the maximum effect can be exhibited in terms of electron transfer area and electrolyte wetting. Specifically, when the sulfur is thinly and evenly loaded to the above-mentioned area range inside the porous carbon material and on the outer surface of the porous carbon material, the electron transfer contact area during charge and discharge can be increased. When the sulfur is located in an area corresponding to 100% of the interior of the porous carbon material and the outer surface of the porous carbon material, the porous carbon material is completely covered by the sulfur, resulting in poor electrolyte wetting, little or no contact, and thus unable to accept electrons and participate in electrochemical reactions.

[0126] The sulfur-carbon composite may, for example, contain sulfur in an amount of 65 wt % or more, specifically 65 to 90 wt %, 70 to 85 wt % or 72 to 80 wt %, based on 100 wt % of the sulfur-carbon composite. When the sulfur content is within the above range, it may have a favorable effect on the performance and capacity of the battery, but the present disclosure is not limited thereto.

[0127] The sulfur-carbon composite of the present disclosure can be manufactured by any method commonly used in the art without limitation. For example, the composite can be prepared by simply mixing the sulfur with the porous carbon material and then heat-treating the mixture.

[0128] In one embodiment of the present disclosure, based on the above composition, the positive electrode active material may further include at least one additive selected from transition metal elements, Group IIIA elements, Group IVA elements, compounds of these elements with sulfur, and alloys of these elements with sulfur.

[0129] The transition metal element may include Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Y, Zr, Nb, Mo, Tc, Ru, Rh, Pd, Os, Ir, Pt, Au or Hg, the IIIA group element may include Al, Ga, In, Ti, etc., and the IVA group element may include Ge, Sn, Pb, etc.

[0130] Based on the total weight of the positive electrode active material layer, the positive electrode for the lithium secondary battery of the present disclosure may contain, for example, 80% by weight or more, specifically 80% by weight to 100% by weight, more specifically 85% by weight to 98% by weight, or 80% by weight to 95% by weight of the positive electrode active material. Based on the total 100% by weight of the positive electrode active material layer, the lower limit of the amount of the positive electrode active material may be 70% by weight or more or 85% by weight or more, and based on the total 100% by weight of the positive electrode active material layer, the upper limit may be 99% by weight or less or 90% by weight or less. The amount of the positive electrode active material can be set by a combination of a lower limit and an upper limit. When the amount of the positive electrode active material is less than the above range, the relative amount of auxiliary materials such as conductive materials and adhesives is high, while the amount of the positive electrode active material is low, which makes it difficult to achieve a battery with high capacity and high energy density. On the contrary, when the amount of the sulfur-carbon composite exceeds the above range, the relative amount of the conductive material or adhesive as described below is low, and the physical properties of the electrode are reduced.

[0131] The conductive material serves as a movement path of electrons from the current collector to the positive active material by electrically connecting an electrolyte to the positive active material, and may include any material having conductive properties as an electrode component physically different from carbon contained in the sulfur-carbon composite without limitation.

[0132] For example, the conductive material may include: carbon black, such as Super-P, Danka black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, carbon black, etc.; carbon derivatives, such as carbon nanotubes, fullerenes, etc.; conductive fibers, such as carbon fibers, metal fibers, etc.; fluorocarbons; metal powders, such as aluminum powder, nickel powder, etc.; or conductive polymers, such as polyaniline, polythiophene, polyacetylene, polypyrrole, etc. (used alone or in combination).

[0133] Based on the total weight of the positive electrode active material, the amount of the conductive material may be 1 to 10 wt %. When the amount of the conductive material is less than the above range, the electron transfer between the positive electrode active material and the current collector is reduced, resulting in lower voltage and capacity. On the contrary, when the amount of the conductive material exceeds the above range, the relative proportion of the positive electrode active material is low, and the total energy (charge) of the battery may be reduced. Therefore, it is preferred to determine the optimal amount within the above range.

[0134] The binder bonds the positive electrode active material to the positive electrode current collector and interconnects the positive electrode active materials to increase bonding strength, and may include any binder known in the art.

[0135] For example, the adhesive may include any one selected from the group consisting of: a fluororesin-based adhesive, including polyvinylidene fluoride (PVdF), a polyvinylidene fluoride-based polymer containing at least one vinylidene fluoride as a repeating unit, polytetrafluoroethylene (PTFE) or a mixture thereof; a rubber-based adhesive, including styrene-butadiene rubber (SBR), acrylonitrile-butadiene rubber and styrene-isoprene rubber; an acrylic-based adhesive; a cellulose-based adhesive, including carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose and regenerated cellulose; a polyol-based adhesive; a polyolefin-based adhesive, including polyethylene and polypropylene; a polyimide-based adhesive; a polyester-based adhesive; and a silane-based adhesive; and a mixture thereof or a copolymer thereof.

[0136] In one embodiment of the present disclosure, the binder may include polyacrylic acid (PAA).

[0137] Based on the total weight of the positive electrode active material layer, the amount of the binder may be 1 to 10 wt %. When the amount of the binder is less than the above range, the physical properties of the positive electrode may be reduced, and the positive electrode active material and the conductive material may be desorbed. When the amount of the binder exceeds the above range, the relative proportion of the positive electrode active material and the conductive material in the positive electrode is low, resulting in low battery capacity. Therefore, it is preferred to determine the optimal amount within the above range.

[0138] In the present disclosure, a method of manufacturing the positive electrode for a lithium secondary battery is not particularly limited, and may include any method known to those skilled in the art or a modification thereof.

[0139] For example, the positive electrode for a lithium secondary battery may be manufactured by preparing a positive electrode slurry composition having the above composition, and coating the positive electrode slurry composition on at least one surface of the positive electrode collector to form the positive electrode active material layer.

[0140] The positive electrode slurry composition includes the positive electrode active material described above, and may further include the binder, the conductive material, and a solvent.

[0141] The solvent includes any solvent that promotes uniform dispersion of the positive electrode active material. The solvent may include an aqueous solvent, most preferably water, and in this case, the water may be distilled water or deionized water. However, the present disclosure is not necessarily limited thereto, and if desired, a lower alcohol that is easily mixed with water may be used. The lower alcohol may include methanol, ethanol, propanol, isopropanol and butanol, and preferably, a mixture of a lower alcohol and water may be used.

[0142] The solvent may be included at a sufficient concentration level to facilitate coating, and the specific amount may vary depending on the coating method and apparatus.

[0143] If necessary, the positive electrode slurry composition may further include materials commonly used in the corresponding technical field to improve functions. For example, the materials may include a viscosity modifier, a flow aid, a filler, and the like.

[0144] The method of coating the positive electrode slurry composition is not particularly limited in the present disclosure, and may include, for example, doctor blade, die casting, comma coating, screen printing, etc. In addition, the positive electrode slurry may be coated on the positive electrode current collector by pressing or laminating after forming on a separate substrate.

[0145] After the coating, a drying process may be performed to remove the solvent. The drying process may be performed at a suitable temperature and time to remove the solvent, and the conditions may vary depending on the type of solvent and are not particularly limited in the present disclosure. For example, the drying method may include drying with warm air, hot air or low humidity air, vacuum drying, and drying by (far) infrared radiation or electron beam radiation, etc. The drying speed is usually adjusted to remove the solvent as quickly as possible within a speed range where cracking does not occur in the positive active material layer due to stress concentration or the positive active material layer is peeled off from the positive current collector.

[0146] In addition, after the drying, the current collector may be pressed to increase the density of the positive electrode active material in the positive electrode. The pressing method may include molding, rolling, and the like.

[0147] The positive electrode, specifically the positive electrode active material layer manufactured by the above composition and manufacturing method, may have a porosity of 50 to 80 volume %, specifically 60 to 75 volume %. When the porosity of the positive electrode is less than 50 volume %, the filling level of the positive electrode slurry composition comprising the positive electrode active material, the conductive material and the binder is too high, so that it is impossible to maintain enough electrolyte for showing ionic conductivity and / or conductivity in the positive electrode active material. As a result, the output characteristics or cycle characteristics of the battery may deteriorate, which causes severe overvoltage and discharge capacity reduction of the battery. On the contrary, when the porosity of the positive electrode is too high and exceeds 80 volume %, it may cause poor physical and electrical connection with the collector, low adhesion strength and no or small reactivity, and electrolyte filling at high porosity may reduce the energy density of the battery. Therefore, the porosity is appropriately adjusted within the above range.

[0148] negative electrode

[0149] The negative electrode may include a negative electrode current collector and a negative electrode active material layer on one or both surfaces of the negative electrode current collector. Alternatively, the negative electrode may be a lithium metal plate.

[0150] The negative electrode current collector is configured to support the negative electrode active material layer as described in the positive electrode current collector.

[0151] The negative electrode active material layer may include a negative electrode active material, and may further include a conductive material, a binder, etc. In this case, the conductive material and the binder follow the above description.

[0152] The negative electrode active material may include a material capable of reversibly inserting or releasing lithium (Li + ), a material capable of reacting with lithium ions to reversibly form a lithium-containing compound, lithium metal or a lithium alloy.

[0153] The reversible insertion and extraction of lithium ions (Li + ) may include, for example, crystalline carbon, amorphous carbon or a mixture thereof. + ) to reversibly form a lithium-containing compound may include, for example, tin oxide, titanium nitrate or silicon. The lithium alloy may include, for example, an alloy of lithium (Li) and a metal selected from the group consisting of sodium (Na), potassium (K), rubidium (Rb), cesium (Cs), francium (Fr), beryllium (Be), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), radium (Ra), aluminum (Al) and tin (Sn).

[0154] Preferably, the negative electrode active material may be lithium metal, specifically, may be in the form of lithium metal foil or lithium metal powder.

[0155] Diaphragm

[0156] The separator separates or insulates the positive electrode from the negative electrode and enables lithium ions to be transferred between the positive electrode and the negative electrode. The separator may be made of a porous non-conductive or insulating material, not limited to a particular type, and may include any separator commonly used in lithium secondary batteries. The separator may be an independent component such as a membrane, and may also be a coating added to the positive electrode and / or the negative electrode.

[0157] The separator may preferably have low resistance to the movement of electrolyte ions and high electrolyte absorption capacity.

[0158] The separator may include a porous substrate, and the porous substrate may include any porous substrate commonly used in secondary batteries, and a porous polymer film may be used alone or in a stacked manner. For example, a non-woven fabric made of high melting point glass fiber, polyethylene terephthalate fiber, etc., or a polyolefin-based porous film may be used, but is not limited thereto.

[0159] In the present disclosure, the porous substrate is not limited to a specific material and may include any porous substrate commonly used in electrochemical devices. For example, the porous substrate may include at least one type of material selected from the group consisting of polyolefins (such as polyethylene, polypropylene, etc.), polyesters (such as polyethylene terephthalate, polybutylene terephthalate, etc.), polyamides, polyacetals, polycarbonates, polyimides, polyetheretherketones, polyethersulfones, polyphenylene oxides, polyphenylene sulfides, polyethylene naphthalate, polytetrafluoroethylene, polyvinylidene fluoride, polyvinyl chloride, polyacrylonitrile, cellulose, nylon, poly(p-phenylene benzobisoxazole), and polyarylates.

[0160] The thickness of the porous substrate may be 1 to 100 μm, preferably 5 to 50 μm, but is not limited thereto. Although the thickness of the porous substrate is not limited to the above range, when the thickness is too much less than the above lower limit, the mechanical properties may be reduced and the separator may be easily damaged when the battery is used.

[0161] The porous substrate may have an average pore diameter of 0.001 to 50 μm and a porosity of 10 to 95 volume %, but is not limited thereto.

[0162] The lithium-sulfur battery according to the present disclosure may adopt a commonly used winding process and a lamination or stacking and folding process of a separator and an electrode.

[0163] The lithium-sulfur battery is not limited to a specific shape and may have various shapes, for example, a cylindrical shape, a stacked type, a coin type, a pouch type, and the like.

[0164] Hereinafter, exemplary embodiments are presented to help understand the present disclosure, but the following embodiments only describe the present disclosure by way of example, and it is obvious to those skilled in the art that various modifications and changes can be made within the scope and technical aspects of the present disclosure, and such modifications and changes fall within the scope of the appended claims.

[0165] [Manufacturing of lithium-sulfur batteries]

[0166] Example 1

[0167] Preparation of electrolyte for lithium-sulfur batteries

[0168] 0.5 M lithium bis(fluorosulfonyl)imide (LiFSI), 4 wt % lithium nitrate (LiNO3, molar mass 69 g / mol) and 1 wt % dipyridyl disulfide (PyDS, molar mass 220.31 g / mol) were added to a mixture (8:2 v / v) of 1,2-dimethoxyethane (DME) and 2-methylfuran (2MeF) and stirred at room temperature (23°C) for 12 h to prepare an electrolyte.

[0169] <Structural formula of PyDS>

[0170]

[0171] 2,2 - Dipyridyl disulfide

[0172] Electrode preparation

[0173] The sulfur - carbon composite (S8:CNT = 70:30 by weight), which is used as the positive electrode active material, and polyacrylic acid (PAA), which is used as the binder, are mixed at a weight ratio of 96:4 in distilled water, which is used as the solvent, to prepare a positive electrode paste.

[0174] The positive electrode paste is coated on both surfaces of a 12 - μm - thick aluminum current collector, dried at 80 °C, and rolled using a roll press to prepare a positive electrode. In this case, the loading amount of the positive electrode active material is 3.3 mAh / cm 2 , and the porosity of the positive electrode active material layer excluding the current collector from the positive electrode is 74% by volume.

[0175] For the negative electrode, a 50 - μm - thick lithium metal foil is prepared.

[0176] Lithium-sulfur battery manufacturing

[0177] The positive electrode and the negative electrode prepared as above are placed and stacked with a polyethylene separator having a thickness of 16 μm and a porosity of 68% by volume interposed therebetween to assemble a pouch - type single cell, and 1 g of the prepared electrolyte is injected so that the ratio of electrolyte / S loading amount (El / S) is 2.5 g / g, and then sealed to manufacture a pouch - type lithium - sulfur battery.

[0178] Example 2

[0179] A lithium - sulfur battery is manufactured by the same method as in Example 1, except that 3% by weight of dipyridyl disulfide (PyDS) is added.

[0180] Comparative Example 1

[0181] A lithium - sulfur battery is manufactured by the same method as in Example 1, except that dipyridyl disulfide (PyDS) is not added.

[0182] Comparative Example 2

[0183] The electrolyte was prepared by the same method as in Example 1, except that ethylene carbonate (EC): dimethyl carbonate (DMC) (1:2 volume / volume) was used instead of DME: 2-MeF (8:2 volume / volume) for the non-aqueous solvent. In Comparative Example 2, it was confirmed that lithium nitrate (LiNO3) was not dissolved and could not be used as an electrolyte for a lithium-sulfur battery.

[0184] Comparative Example 3

[0185] A lithium-sulfur battery was manufactured by the same method as in Example 1, except that, for the non-aqueous solvent, 1,2-dimethoxyethane (DME):1,3-dioxolane (DOL) (5:5 v / v) was used instead of DME:2-MeF (8:2 v / v).

[0186] Comparative Example 4

[0187] A lithium-sulfur battery was manufactured by the same method as in Example 1, except that, for the non-aqueous solvent, 1,2-dimethoxyethane (DME):2-methyltetrahydrofuran (2-Me-THF) (8:2 v / v) was used instead of DME:2-MeF (8:2 v / v).

[0188] Experimental Example 1. Battery performance evaluation and results

[0189] The performance of each battery of Example 1, Example 2 and Comparative Example 1 was evaluated by the following method. In the case of Comparative Example 2, since the nitrate in the electrolyte was not dissolved as described above, the battery performance evaluation result was omitted.

[0190] The battery performance was evaluated by repeating the charge-discharge cycle of 0.1 C charge / 0.1 C discharge three times at 25°C under the cutoff condition of 1.8 V to 2.5 V, followed by 0.2 C charge / 0.1 C discharge. Figure 1 and Figure 2 The results are shown.

[0191] Figure 1 The number of cycles until the capacity decays to 90% by repeated charge and discharge cycles is shown, with the capacity at the fifth cycle after the capacity is stabilized being 100%.

[0192] refer to Figure 1 It was confirmed that Example 1 achieved a capacity retention rate of 90% at 54 cycles, Example 2 at 45 cycles, and Comparative Example 1 at 40 cycles.

[0193] Through experiments, it was confirmed that the batteries of Example 1 and Example 2 suppressed capacity decay and improved capacity retention rate in repeated charge and discharge cycles, and reached a capacity retention rate of 90% at a later time than that of Comparative Example 1.

[0194] Figure 2 The change in coulombic efficiency per unit weight during repeated charge and discharge cycles is shown.

[0195] refer to Figure 2 , it was confirmed that the coulombic efficiency of lithium-sulfur batteries decreases rapidly during repeated charge and discharge cycles due to the shuttling effect of lithium polysulfides. In this case, the batteries of Example 1 and Example 2 using PyDS in the electrolyte showed a significant delay in the decrease of coulombic efficiency compared to the battery of Comparative Example 1 without PyDS.

[0196] Experimental Example 2. Battery Performance Evaluation and Results

[0197] The performance of each battery of Example 1, Comparative Example 3, and Comparative Example 4 was evaluated by the following method.

[0198] The battery performance was evaluated by repeating the charge-discharge cycle of 0.1 C charge / 0.1 C discharge three times at 25°C under the cutoff condition of 1.8 V to 2.5 V, followed by 0.2 C charge / 0.1 C discharge. Figure 1 and Figure 2 The results are shown.

[0199] Figure 3 The number of cycles until the capacity decays to 90% by repeated charge and discharge cycles is shown, with the capacity at the fifth cycle after the capacity is stabilized being 100%.

[0200] refer to Figure 3 It was confirmed that Example 1 achieved a capacity retention rate of 90% in 54 cycles, Comparative Example 3 in 24 cycles, and Comparative Example 4 in 15 cycles.

[0201] In this case, Comparative Examples 3 and 4 include the aryl derivative according to the embodiment of the present disclosure in the electrolyte composition, but include a non-conjugated heterocyclic compound instead of the conjugated heterocyclic compound as the nonaqueous solvent.

[0202] Through experiments, it was confirmed that when the aryl derivative according to one embodiment of the present disclosure is included in the electrolyte of the lithium-sulfur battery, the conjugated heterocyclic compound such as 2-methylfuran should be included as the non-aqueous solvent.

Claims

1. An electrolyte for a lithium-sulfur battery, comprising: Non-aqueous solvents, lithium salts, nitrates / esters and aromatic derivatives, wherein the nonaqueous solvent comprises a linear ether compound and a conjugated heterocyclic compound, and The aryl derivative comprises a compound represented by the following Chemical Formula 1, a compound represented by the following Chemical Formula 2, a compound represented by the following Chemical Formula 3, or a mixture thereof: [Chemical formula 1] R1-S - [Chemical formula 2] R2-SH [Chemical formula 3] R3-SS-R4 In the chemical formulae 1 to 3, R1 to R4 are each independently a 5- or 6-membered heteroaryl group containing at least one N or S atom as a ring atom.

2. The electrolyte for lithium-sulfur batteries according to claim 1, wherein R1 to R4 are each independently an orthopyridyl group.

3. The electrolyte for lithium-sulfur batteries according to claim 1, wherein the aryl derivative comprises 2,2 -Bispyridyl disulfide. 4 . The electrolyte for a lithium-sulfur battery according to claim 1 , wherein the content of the aryl derivative is 0.1 wt % to 5 wt % based on the total weight of the electrolyte for a lithium-sulfur battery. 5 . The electrolyte for a lithium-sulfur battery according to claim 1 , wherein the content of the aryl derivative is 1 wt % to 3 wt % based on the total weight of the electrolyte for a lithium-sulfur battery. 6 . The electrolyte for lithium-sulfur batteries according to claim 1 , wherein a weight ratio of the aryl derivative to the nitrate (the aryl derivative / the nitrate) is 0.2 to 1.

5. 7 . The electrolyte for a lithium-sulfur battery according to claim 1 , wherein the content of the linear ether compound and the conjugated heterocyclic compound is 80% by volume or more based on the total weight of the nonaqueous solvent. 8 . The electrolyte for lithium-sulfur batteries according to claim 1 , wherein the conjugated heterocyclic compound is a conjugated cyclic ether compound. 9 . The electrolyte for lithium-sulfur batteries according to claim 1 , wherein the nonaqueous solvent does not contain a carbonate-based solvent.

10. The electrolyte for lithium-sulfur batteries according to claim 1, wherein the cation of the nitrate is an alkali metal.

11. A lithium-sulfur battery comprising: A positive electrode; a negative electrode; a separator located between the positive electrode and the negative electrode; and an electrolyte according to any one of claims 1 to 10. 12 . The lithium-sulfur battery according to claim 11 , wherein the positive electrode comprises a sulfur-containing compound as a positive electrode active material.

13. The lithium-sulfur battery according to claim 12, wherein the sulfur-containing compound comprises inorganic sulfur (S8), lithium (poly)sulfide (Li2S n , 1≤n≤8), carbon-sulfur polymer ((C2S x ) m , 2.5≤x≤50, 2≤m) or a mixture thereof. 14 . The lithium-sulfur battery according to claim 11 , wherein the negative electrode comprises lithium metal, lithium alloy or a mixture thereof as a negative electrode active material. 15 . The lithium-sulfur battery according to claim 11 , wherein the lithium-sulfur battery is a coin-type battery, a pouch-type battery, or a cylindrical battery.